Application of Logistics Management in Disaster Management at Cianjur Regional General Hospital in 2023 - Ayu Laili Rahmiyati; Elda Permatasari; Suhat Suhat; Asep Dian Abdilah (Jurnal Health Sains, 2024)
Disaster logistics management is an effort to arrange logistics raw materials in the implementation of disaster management, which consists of planning, procurement, storage, distribution, transportation, and receiving. Cianjur Hospital is one of the health facilities affected by the Cianjur earthquake; due to the earthquake, almost all parts of the hospital were damaged, so some health services were carried out in emergency tents. The purpose of this study was to obtain an analysis of the disaster logistics management system at RSUD Cianjur. The design used is qualitative with a descriptive approach. The informants in this study were 5 employees of Cianjur Hospital. Data collection is carried out through in-depth interviews, document studies, and observations. Analysis data processing uses data reduction analysis, data presentation, and conclusions. The results showed that the disaster logistics management system at Cianjur Hospital had appropriate planning, but there was little difficulty meeting needs. At the time of procurement and/or receipt, there is a discrepancy in needs and an unclear identity of the sender. There are two logistics warehouses, namely inside the building and in the emergency tent, but the warehouse security in the emergency tent is less safe and the place is inadequate. In distribution, there is speed, accuracy, and the amount of distribution that is sometimes not right. It is recommended that hospitals optimize the performance of each human resource as well as write SOPs regarding disaster logistics management systems.